Anabolic androgenic steroid abuse in the United Kingdom: An update - Mullen, Carrie (Br J Pharmacol, 2020)
Anabolic androgenic steroids (AASs) are prescribed for medical conditions related to low testosterone. Abuse of AASs has surged as they become recognised as potent image enhancement drugs. The primary goal of most abusers is to obtain a more attractive outward appearance. Abuse is complex. There are a vast range of AAS substances illegally available, the nature of their true composition is difficult to evaluate. Users follow dosing patterns which incorporate a number of different AASs, in addition to other pharmaceutical substances believed to complement the desired physical effects or manage unwanted effects. Animal work and medical case reports suggest potential to cause serious hepatotoxicity, plus possible neurotoxicity, nephrotoxicity and damage to the cardiovascular and reproductive systems. As the long‐term AASs users reach maturity, further controlled experimentation, with larger sample sizes, is required. Data gathering should be directed towards the most vulnerable group of AAS users, females and adolescent boys.